FORMATION OF PROFESSIONAL COMPETENCE FUTURE TEACHERS OF TECHNOLOGY - Z.S. Kucher (Academy of Cognitive and Natural Sciences, 2008)
The problem of the professional competence of the future teachers technological nowadays is considered.